Portability of firm corporate governance in mergers and acquisitions - Hussain, Tanveer (2022)
We study the corporate governance portability from bidders to targets in Mergers and Acquisitions and its impact on bidder announcement returns. We find that the bidder’s cumulative abnormal returns are higher in acquisitions where the bidder’s corporate governance quality exceeds that of the target. This result suggests a positive valuation effect for bidder shareholders resulting from the portability of good firm corporate governance from bidders to targets. We also find that this effect is stronger when bidders are domiciled in countries with better corporate governance. The results pass several robustness tests, including alternative measures of firm corporate governance and different sample periods.